137,200 engineers needed by 2010 - Ridzwan , Abdullah (The New Straits Times Press (M) Berhad, 2002)
PEKAN, Sat. - Malaysia will need 137,200 engineers and 331,700 assistant engineers by 2010, Education Minister Tan Sri Musa Mohamad said today.